2016
DOI: 10.1039/c6cp03070j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid surfactants decorated with copper ions: aggregation behavior, antimicrobial activity and anti-proliferative effect

Abstract: In the present study, the emphasis is laid on the self aggregation behavior of copper based inorganic-organic hybrids in aqueous media. The two complexes, cationic hexadecyl pyridinium trichloro cuprate (1 : 1), [Cp](+)[CuCl3](-), and bishexadecylpyridinium tetrachloro cuprate (2 : 1), [Cp2](2+)[CuCl4](2-), were synthesized using the ligand insertion method. The complexes were characterized using elemental analysis, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), nuclear magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Copper ions attack the bacteria at different sites[44-46]. They can interact with the outer membrane of bacteria and subsequently disintegrate the bacterial cell wall which is known as the bacteriolytic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Copper ions attack the bacteria at different sites[44-46]. They can interact with the outer membrane of bacteria and subsequently disintegrate the bacterial cell wall which is known as the bacteriolytic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Cu‐CPC with molecular formula [CP] 2 + [CuCl 4 ] 2− was synthesized as reported previously . Briefly, CuCl 2 ⋅ 2 H 2 O and CPC were mixed in a 1:2 molar ratio in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…proposed the use of cetylpyridinium tetrachlorozincate as a titrant for analysis of anionic surfactants. , In 2015, Kaur et al . synthesized (CP) 2 CuCl 4 and (CP)­CuCl 3 and demonstrated that the insertion of copper into the CPC moiety enhanced the antibacterial activity as compared to pure CPC . Although the antimicrobial properties of copper (Cu) have long been known, the realization of the Cu–cetylpyridinium conjugate technology for healthcare applications would be extremely challenging due to the potential for blue ( e.g ., Cu 2+ ) or yellow ( e.g ., [CP]­[CuCl 3 ] or [CP] 2 [CuCl 4 ]) staining associated with the d-orbital splitting of the copper ion.…”
Section: Introductionmentioning
confidence: 99%